Controlling Photoluminescence Enhancement and Energy Transfer in WS2:hBN:WS2 Vertical Stacks by Precise Interlayer Distances. Issue 3 (18th December 2019) - Xu, Wenshuo; Kozawa, Daichi; Zhou, Yingqiu; Wang, Yizhi; Sheng, Yuewen; Jiang, Tian; Strano, Michael S.; Warner, Jamie H.
Abstract: 2D semiconducting transition metal dichalcogenides (TMDs) are endowed with fascinating optical properties especially in their monolayer limit. Insulating hBN films possessing customizable thickness can act as a separation barrier to dictate the interactions between TMDs. In this work, vertical layered heterostructures (VLHs) of WS2 :hBN:WS2 are fabricated utilizing chemical vapor deposition (CVD)‐grown materials, and the optical performance is evaluated through photoluminescence (PL) spectroscopy. Apart from the prohibited indirect optical transition due to the insertion of hBN spacers, the variation in the doping level of WS2 drives energy transfer to arise from the layer with lower quantum efficiency to the other layer with higher quantum efficiency, whereby the total PL yield of the heterosystem is increased and the stack exhibits a higher PL intensity compared to the sum of those in the two WS2 constituents. Such doping effects originate from the interfaces that WS2 monolayers reside on and interact with. The electron density in the WS2 is also controlled and subsequent modulation of PL in the heterostructure is demonstrated by applying back‐gated voltages. Other influential factors include the strain in WS2 and temperature. Being able to tune the energy transfer in the VLHs may expand the development of photonic applications in 2D systems. Abstract : Vertical heterostructures of WS2 :hBN:WS2 exhibit photoluminescence enhancement due to interlayer energy transfer, derived from differences in the doping levels. The interlayer interactions are tuned by accurately controlling the thickness of the hBN barrier between the two WS2 vertical stacked layers, along with the strain in WS2 and temperature.